Develop Reusable Carbon Sub‐Micrometer Composites with Record‐High Cd(II) Removal Capacity - Mengke Cui; Huiting Jiao; Shijie Yuan; Bin Dong; Zuxin Xu (Advanced Science)
Abstract Cd(II)‐induced pollution across diverse water bodies severely threatens ecosystems and human health. Nevertheless, achieving ultra‐efficient and cost‐effective treatment of trace amounts of heavy metals remains a major challenge. Herein, the novel carbon sub‐micrometer composites (CSMCs) supported Fe0@γ‐Fe2O3 core‐shell clusters nanostructures are designed and synthesized through a series of universally applicable methods. Research data on adsorption behavior clearly revealed that resorcinol/formaldehyde 1.25‐basic ferric acetate (RF‐1.25BFA) and RF‐1.25BFA‐540 have surprising adsorption capacities. Employing the adsorbent dosage of 0.025 g L−1, the adsorption capacities for 10 mg L−1 Cd(II) reached 400.00 mg g−1 with ultrafast adsorption kinetics, alongside theoretical maximum adsorption capacities for Cd(II) of 1108.87 and 1065.06 mg g−1 using 0.025 g L−1 adsorbent, respectively, setting a new record‐high level. Additionally, they demonstrated exceptional stability and reusability, maintaining Cd(II) removal efficiency above 95% even after 15 adsorption–desorption cycles. Importantly, this study is the first to unveil a new ultrafast successive two‐step enrichment–hydrolysis adsorption mechanism for Cd(II) removal, emphasizing the critical role played by iron clusters nanostructures in constructing a high‐alkalinity adsorption microenvironment on the surface of the materials. The findings reported pioneered a new avenue for the rational design of high‐performance environmental remediation materials, aiming to overcome the limitations of traditional mine drainage treatment.